2007
DOI: 10.1139/w07-036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flavones and flavonols on colonization of tomato plants by arbuscular mycorrhizal fungi of the genera Gigaspora and Glomus

Abstract: No clear data are available on how flavonoids from different chemical groups affect root colonization by arbuscular mycorrhizal fungi (AMF) and whether flavonoids affecting the presymbiotic growth of AMF also affect root colonization by AMF. In the present work, we compared the effect of flavones (chrysin and luteolin) and flavonols (kaempferol, morin, isorhamnetin, and rutin) on root colonization (number of entry points and degree of root colonization) of tomato plants (Lycopersicum esculentum L.) with the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 30 publications
2
37
0
2
Order By: Relevance
“…Flavonoids were shown to stimulate spore germination, hyphal branching and root colonization (Kikuchi et al 2007;Scervino et al 2005Scervino et al , 2007Siqueira et al 1991;Steinkellner et al 2007). Among flavonoids in tomato root exudates, chrysin, luteolin and morin increased the number of entry points and the root colonization of Gigaspora rosea, Gigaspora margarita, Glomus mosseae, and Glomus intraradices, whereas kaempferol, isorhamnetin, and rutin showed no effect (Scervino et al 2007). In addition, a M. truncatula mutant with coumestrol accumulation was found to be hyperinfected by AMF (Morandi et al 2009).…”
Section: Interaction With Arbuscular Mycorrhizal Fungimentioning
confidence: 99%
“…Flavonoids were shown to stimulate spore germination, hyphal branching and root colonization (Kikuchi et al 2007;Scervino et al 2005Scervino et al , 2007Siqueira et al 1991;Steinkellner et al 2007). Among flavonoids in tomato root exudates, chrysin, luteolin and morin increased the number of entry points and the root colonization of Gigaspora rosea, Gigaspora margarita, Glomus mosseae, and Glomus intraradices, whereas kaempferol, isorhamnetin, and rutin showed no effect (Scervino et al 2007). In addition, a M. truncatula mutant with coumestrol accumulation was found to be hyperinfected by AMF (Morandi et al 2009).…”
Section: Interaction With Arbuscular Mycorrhizal Fungimentioning
confidence: 99%
“…After spore germination, the AM fungal hyphae grows towards the host plant roots [58,59], followed by penetration into the root cortical cells and leading to formation of intra-radical structures. Scervino et al [60,61] reported a close relationship between the number of entry points and the degree of colonization.…”
Section: Effect Of Different Carrier Treatments On Re-inoculation/colmentioning
confidence: 95%
“…Letras diferentes indican diferencias estadísticamente significativas (P ≤ 0,05), de acuerdo con la prueba de Tukey. Muchos estudios se han realizado sobre el efecto de los flavonides en la etapa pre-simbiótica y simbiótica de los HFMA; la mayoría se han realizado con hongos del género Gigaspora, en menor grado con especies de Glomus y prácticamente nada con otros géneros (Morandi, 1996;Vierheilig et al, 1998;scervino et al, 2005a;2005b;2006;2007;. La quercetina es el flavonoide más ampliamente distribuido en las plantas micorrizadas y tienen un efecto positivo en la germinación de las esporas y la longitud de las hifas (tsai y Phillips, 1991;bécard et al, 1992;chabot et al, 1992;Kape et al, 1992;bel-rhlid et al, 1993;Poulin et al, 1997).…”
Section: Germinación De Esporas Y Fragmentos De Raíces Con Vesículas unclassified